La Nasalisation des Occlusives à la Périphérie syllabique en Karitiana et en Urueuwauwau (Polifonia, 2003)
ABSTRACT: Our analysis of the underlying phonological system of two Amazonian languages checks over the Piggot’s universal typological claim that a language can’t own simultaneous oppositions between oral versus nasal voiced stops and between oral versus nasal vowels. The virtual syllabic break – as a psychophonic echo of the actualized pause – is the deciding factor of the syllable periphery nasalization.